KEPENTINGAN INDONESIA MEMBERLAKUKAN KEBIJAKAN BEA MASUK TINDAKAN PENGAMANAN (BMTP) PERDAGANGAN TERHADAP IMPOR UBIN KERAMIK (STUDI KASUS : IMPOR UBIN KERAMIK DARI TIONGKOK) - Muhammad Soleh; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study describes the trade liberalization which causes a Threat of loss for the domestic industries. Hence, the country implements protectionism policies against its industry from the Threat of imports. This research discusses the interests of Indonesia in imposing an import duty policy of trade safeguard measures on the import of ceramic tiles (case study: the import of ceramic tiles from Tiongkok).This qualitative research uses the descriptive explanative method, in which the data sources were taken from; books, journals, official articles, mass media, and official websites. The perspective used by the writer in this thesis is the perspective of Mercantilism with the the nation-state level of analysis and the theory used is the theory of protectionism, it can be seen from the efforts of the country to protect the domestic ceramic tiles industries from the threat of ceramic tiles imports from Tiongkok by implementing import duty policy of trade safeguards measures.The results of this study decribes that Indonesia imposed an import duty policy of trade safeguards measures against the import of ceramic tiles is to protect the ceramic tile industries from threat of imports which are cheaper than local ceramic tiles, which causes domestic industries to be threatened in the form of serious losses that is financial losses. Keywords : Import Duty, Safeguard Measures, National Interest, Protectionism, Mercantilism Perspective